Too Great a Burden to Bear : The Struggle and Failure of the Freedmen's Bureau in Texas - Bean, Christopher B. (Book collections on Project MUSE., 2017)
In its brief seven-year existence, the Freedmen's Bureau became the epicenter of the debate about Reconstruction. Historians have only recently begun to focus on the Bureau's personnel in Texas, the individual agents termed the 'hearts of Reconstruction'. Specifically addressing the historiographical debates concerning the character of the Bureau and its sub-assistant commissioners (SACs), this title sheds new light on the work and reputation of these agents.